A school-based feasibility study of method of levels: a novel form of client-led counselling. (2nd October 2019) - Churchman, Anamaria; Mansell, Warren; Tai, Sara
ABSTRACT: The purpose of this study was to test the feasibility and acceptability of a novel psychological therapy (Method of Levels) amongst adolescents experiencing psychological distress. An initial estimated effect size and a clinical significance analysis were undertaken which will help inform future studies. A case-series of 16 participants utilised the YP-CORE as a primary outcome measure. Data was collected at baseline, on completion of therapy (six months) and two and four months after completion of the therapy. Young people used a self-booking system to access sessions. Additionally, young people had full control over the content and length of the sessions. A total of 14 participants reported that the therapy was acceptable to them and 12 participants were retained for the entire course of the study. The self-booking system was successfully used with young people attending on average 6–8 sessions. Analysis of clinically significant change for the YP-CORE at therapy completion indicated that five students recovered and seven experienced no change; this was largely maintained at follow up. Effect size estimations were medium-to-large. Initial findings suggest that Method of Levels is a feasible and acceptable form of counselling for young people within the school setting. Moreover, positive preliminary effectiveness outcomes suggest that a randomised control study should be considered.